COVERING SIZES IN HEALTHY AND PATIENTS WITH SINUSITIS BOYS AND MEN WITH ACUTE PURULENT - Школьнік, Е.Я. (World of Medicine and Biology, 2014)
This article іt has been proved that most of the studied dimensions are more important in healthy young men and women, compared with patients with acute purulent sinusitis boys and men. We installed craniotype-typological differences of covering body size for most parameters - larger in patient’s men and boys brachycephal. Identified also age differences of investigated parameters - higher values in healthy and patients men in general and healthy men different craniotype compared to boys appropriate comparison group.
Keywords: covering body size; craniotype; boys; men; acute purulent sinusitis